(untitled) (Global Journal of Science Frontier Research, 2019)
The spinning of sun and earth induces their magnetism poles. The magnetic poles of the sun are periodically flipping like a clock, which means the direction of spinning of the sun changes periodically from clockwise spinning when the sun is active (warm periods on Earth) to coun Earth). Simulating theoretical mathematical models predicted periodic reversal of the magnetic polarity of both the sun and earth. However, the magnetic poles of the earth flip rarely and irregularly, which means the direction of spinning of the earth change rarely and irregularly. Earth satellites found that our Earth is cleft and its center of mass is not in the center. This is probably what causes the direction of spinning of the Earth to change ra ancient texts, explanation is offered of why our earth is cleft.